Pathways for membrane trafficking during cytokinesis. - Strickland, L.I.; Burgess, D.R. (Trends in Cell Biology, 2004)
The molecular mechanisms underlying targeted deposition of new membrane at the advancing furrow of a dividing cell have long been intriguing to cell biologists. Three recent studies have made use of Drosophila cellularization to explore current questions in this field. These findings indicate that both the secretory pathway and endosomal recycling contribute membrane to the advancing furrow. Furthermore, new work reveals that vesicles derived from the Rab11 recycling endosome (RE) promote actin remodeling at the furrow.